Analysis of the Influence of Social Media Marketing and E-WOM on Purchase Decisions Mediated by Brand Awareness and Trust at "X" Ice Cream Outlets - Citrasumidi, Regina Raina Rania; Pasaribu, Lamhot Henry (International Journal of Social Service and Research, 2023)
With the evolution of the times, there has been a rise in the number of internet and social media users, leading to a shift from traditional marketing methods to digital marketing. The aim of this research was to explore how social media marketing and electronic word-of-mouth (e-WOM) affect the choices made in purchasing, with brand awareness and trust serving as mediating factors. Employing a quantitative approach, an online survey was conducted with 200 participants, and data processing was carried out using SmartPLS software. The findings revealed a notable and meaningful connection was observed, showing a positive influence among social media marketing, e-WOM, and purchasing decisions, wherein brand awareness and trust played intermediary roles., specifically in "X" ice cream outlets. Notably, brand awareness and trust were identified to have a partially mediating effect concerning the connection among social media marketing, e-WOM, and purchasing decisions, this study underscores the managerial significance of improving social media marketing, e-WOM, trust, and brand awareness to positively impact purchase choices.